2018
DOI: 10.4314/jab.v122i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Réponse du soja (<i>Glycine max</i> L.) à des doses croissantes du DAP et Urée au Sud-Kivu, RD Congo

Abstract: La présente étude a été menée pour évaluer la réponse du soja à des doses croissantes du DAP et de l'Urée dans les conditions édapho-climatiques de Bugorhe dans les hautes altitudes du Sud-Kivu. Méthodologie et résultats : Une expérimentation a été conduite suivant un dispositif en parcelle divisée (split plot) avec la source d'engrais azoté et la dose d'application des engrais comme facteur principal et facteur secondaire respectivement. Trois doses de l'Urée et du Di-Ammonium Phosphate (DAP) ont été appliqué… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(11 reference statements)
2
3
1
Order By: Relevance
“…For each US $ spent in buying DAP, the economic gain in terms of VCR was up to 6-8$ when applying 150 kg ha −1 . The same trend was observed on Nitisols in Ethiopia (Getachew 2009) and on Nitisols in South-Kivu (Zamukulu et al 2018). Beyond 150 kg ha −1 , the grain yield, AE and VCR decreased significantly.…”
Section: Dap Application and Use Of Improved Varieties And Agricultur...supporting
confidence: 73%
See 2 more Smart Citations
“…For each US $ spent in buying DAP, the economic gain in terms of VCR was up to 6-8$ when applying 150 kg ha −1 . The same trend was observed on Nitisols in Ethiopia (Getachew 2009) and on Nitisols in South-Kivu (Zamukulu et al 2018). Beyond 150 kg ha −1 , the grain yield, AE and VCR decreased significantly.…”
Section: Dap Application and Use Of Improved Varieties And Agricultur...supporting
confidence: 73%
“…Ulzen et al (2016) fixed the threshold at VCR = 2 for urea but suggested to integrate inoculation, so that it raises up to 4-6. Our VCR was higher than that of Zamukulu et al (2018) on soybeans and Mushagalusa et al (2016) on common bean in the same study area. This is due to the fact that peas are more expensive than common bean and soybean in the area.…”
Section: Dap Application and Use Of Improved Varieties And Agricultur...contrasting
confidence: 66%
See 1 more Smart Citation
“…Highest yield and its components were obtained when selected common bean varieties were sown under fertilized plots. These results are in agreement with previous studies on common bean [ 1 , 4 , 7 , 9 , 14 , 41 , 42 ] and other grain legumes such as soybean [ 16 ] and peas [ 8 ]. In general, common bean responds positively to the application of N and P fertilizer.…”
Section: Discussionsupporting
confidence: 93%
“…These toxicities can inhibit the growth and activity of nitrogen-fixing bacteria, reducing the ability of common beans to fix nitrogen effectively [ 14 ]. In addition, poor soil fertility is one of the major constraints limiting nutrient availability on depleted soils due to overuse and soil erosion [ 15 , 16 ]. This situation is very limiting for the growth and development of crops such as common beans.…”
Section: Introductionmentioning
confidence: 99%